Effect of laser cleaning parameters on aluminum 6061 surface properties - saleh, Zahraa M.; Taha, Ziad Aeyad (Iraqi Journal of Laser, 2026)
This study investigates the crucial factors influencing laser cleaning processes, with a primary focus on aluminum 6061 surfaces. Laser power emerges as the central determinant, as higher power levels intensify the laser matter interaction, leading to enhanced removal of oxide layers. A Microsecond fiber laser with a wavelength of 1064 nm was used in this study to identify optimal cleaning conditions, comprising parameters such as 3W power, a hatch value of 0.003, a speed of 150 mm/s, and a spot size of 200 µm. Furthermore, the research uncovers intriguing insights into the impact of cleaning speed on oxygen levels, revealing that higher speeds result in increased oxygen levels due to dual heat sources—laser beam and heat transfer from adjacent cleaned lines. The hatch parameter’s role is highlighted in controlling the overlapping ratio, where closer line spacing leads to more effective cleaning and reduced surface oxygen content, while wider line spacing impedes cleaning between lines. Additionally, the study explores the potential enhancement of wear rates through laser cleaning, with material roughness playing a critical role, and notes that cleaned samples exhibit fewer defects in their microstructure compared to their uncleaned counterparts. These findings contribute valuable insights to the field of laser cleaning and its applications in surface treatment and material quality improvement.